WHO and UNICEF estimates of national infant immunization coverage: methods and processes - Anthony Burton; Roeland Monasch; Barbara Lautenbach; Marta Gacic-Dobo; Maryanne Neill; Rouslan Karimov; Lara Wolfson; Gareth Jones; Maureen Birmingham (The World Health Organization, 2009)
WHO and the United Nations Children's Fund (UNICEF) annually review data on immunization coverage to estimate national coverage with routine service delivery of the following vaccines: bacille Calmette-Guérin; diphtheria-tetanus-pertussis, first and third doses; either oral polio vaccine or inactivated polio vaccine, third dose of either; hepatitis B, third dose; Haemophilus influenzae type b, third dose; and a measles virus-containing vaccine, either for measles alone or in the form of a combination vaccine, one dose. The estimates are based on government reports submitted to WHO and UNICEF and are supplemented by survey results from the published and grey literature. Local experts, primarily national immunization system managers and WHO/UNICEF regional and national staff, are consulted for additional information on the performance of specific immunization systems. Estimates are derived through a country-by-country review of available data informed and constrained by a set of heuristics; no statistical or mathematical models are used. Draft estimates are made, sent to national authorities for review and comment and modified in light of their feedback. While the final estimates may not differ from reported data, they constitute an independent technical assessment by WHO and UNICEF of the performance of national immunization systems. These country-specific estimates, available from 1980 onward, are updated annually.